2022
DOI: 10.1073/pnas.2115593119
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of cytoplasm viscoelastic properties to mitotic spindle positioning

Abstract: Cells are filled with macromolecules and polymer networks that set scale-dependent viscous and elastic properties to the cytoplasm. Although the role of these parameters in molecular diffusion, reaction kinetics, and cellular biochemistry is being increasingly recognized, their contributions to the motion and positioning of larger organelles, such as mitotic spindles for cell division, remain unknown. Here, using magnetic tweezers to displace and rotate mitotic spindles in living embryos, we uncovered that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 57 publications
3
61
0
Order By: Relevance
“…Our data suggest that the impact of hydrodynamic coupling becomes pronounced for objects over ~20-30% of cell size, which is the typical size ratio for organelles such as nuclei, mitotic spindles or microtubule asters. Accordingly, in vivo direct or indirect force measurements reported spindle, nuclei and aster drags that largely exceeded Stokes drags calculated from the size of these organelles and cytoplasm viscosity (20,28,34). Other relevant parameters that could impact cytoplasm resistance include organelle shape and porosity especially when considering fibrous-like structures such as asters and spindles (21,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data suggest that the impact of hydrodynamic coupling becomes pronounced for objects over ~20-30% of cell size, which is the typical size ratio for organelles such as nuclei, mitotic spindles or microtubule asters. Accordingly, in vivo direct or indirect force measurements reported spindle, nuclei and aster drags that largely exceeded Stokes drags calculated from the size of these organelles and cytoplasm viscosity (20,28,34). Other relevant parameters that could impact cytoplasm resistance include organelle shape and porosity especially when considering fibrous-like structures such as asters and spindles (21,35).…”
Section: Discussionmentioning
confidence: 99%
“…To reach component sizes closer to cell size, we injected a suspension of soya oil mixed with hydrophobic ~1 µm magnetic beads inside eggs. Upon injection, this suspension formed large magnetized oil droplets that ranged in size from 18 to 45 µm (corresponding to ~20-48% of the cell diameter) (20). We applied calibrated forces, by approaching a magnet tip close to the cell surface.…”
Section: Probing Bulk Cytoplasm Rheology At Multiple Length Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…2c; Methods). To reproduce the experimentally observed nuclear positioning close to the cell center 44,45 , we introduced a restoring force for the nucleus to the geometric cell center (Fig. 2c).…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…Generally, the cytoplasm inside the cell can show visco-elastic properties; see Ref. [157], which might lead to a slow ripening of the condensates. Weiss et al [158] also demonstrated that condensates can be strongly influenced by the cytoskeleton, and anomalous diffusion can arise due to molecular crowding, thus adversely affecting larger condensates and in turn not affecting diffusion across smaller condensates as much.…”
Section: Chapter 5 Comparison With Known Literaturementioning
confidence: 99%